Cultural Effects Rather Than a Bilingual Advantage in Cognition: A Review and an Empirical Study. (22nd August 2018) - Samuel, Steven; Roehr‐Brackin, Karen; Pak, Hyensou; Kim, Hyunji
Abstract: The bilingual advantage hypothesis contends that the management of two languages in the brain is carried out through domain‐general mechanisms, and that bilinguals possess a performance advantage over monolinguals on (nonlinguistic) tasks that tap these processes. Presently, there is evidence both for and against such an advantage. Interestingly, the evidence in favor has been thought strongest in children and older adults, leading some researchers to argue that young adults might be at peak performance levels, and therefore bilingualism is unable to confer an improvement. We conducted a large‐scale review of the extant literature and found that the weight of research pointed to an absence of positive evidence for a bilingual advantage at any age. We next gave a large number of young adult participants a task designed to test the bilingual advantage hypothesis. Reasoning from the literature that young adults from an East Asian (Korean) culture would likely outperform those from a Western (British) culture, we also compared participants on this factor. We found no evidence for a bilingual advantage but did find evidence for enhanced performance in the Korean group. We interpret these results as further evidence against the bilingual advantage hypotheses.